APPARATUS FOR GENERATING A SPATIAL OR SPATIOTEMPORAL IMAGE - DE BRUIN, Jaap; VAN DEN BERG, Cornelis Antonius Theodorus; MELIADO, Ettore-Flavio; STEENSMA, Bart R (2025)
The invention refers to an apparatus (110) for generating a spatial or spatiotemporal image, in particular medical image, of a region of interest within a subject (131). The apparatus comprises a) a radiofrequency data providing unit (111) for providing measured differential radiofrequency data, wherein the measured differential radiofrequency data are indicative of radiofrequency data of different states of the region of interest, wherein the radiofre- quency data are indicative of scatterings of radiofrequency radiation between one or more radiofrequency antennas (121), and b) an image generation unit (112) for generating a spatial or spatiotemporal image of the region of interest within the subject based on the differential radiofrequency data. This provides a medical imaging that allows for a low cost, easy, and comfortable imaging of the organs of a subject and even facilitates medical imaging in a home or outpatient environment. L'invention concerne un appareil (110) de génération d'une image spatiale ou spatiotemporelle, en particulier d'une image médicale, d'une région d'intérêt à l'intérieur d'un sujet (131). L'appareil comprend a) une unité de fourniture de données radiofréquence (111) permettant de fournir des données radiofréquence différentielles mesurées, les données radiofréquence différentielles mesurées indiquant des données radiofréquence d'états différents de la région d'intérêt, les données de radiofréquence indiquant des diffusions de rayonnement radiofréquence entre une ou plusieurs antennes radiofréquence (121), et b) une unité de génération d'images (112) permettant de générer une image spatiale ou spatiotemporelle de la région d'intérêt à l'intérieur du sujet sur la base des données radiofréquence différentielles. L'invention propose une imagerie médicale qui permet une imagerie à faible coût, facile et confortable des organes d'un sujet et qui facilite même l'imagerie médicale dans un environnement domestique ou ambulatoire.